Sustainable Biodiesel Production from Waste Cooking Oil and Chicken Fat as an Alternative Fuel for Diesel Engine - Abdulrahman, Ribwar K. (European Scientific Journal, ESJ, 2017)
In recent decade, the demand for fuel as a source of energy has been dramatic. In fact, many oil and gas reservoirs are declining around the world. The use of fossil fuels such as oil, coal, and natural gas is contributing to the phenomenon of global warming. This is because it emits high quantities of carbon dioxide and other greenhouse gases to the atmosphere. Thus, many researchers and energy companies are investigating the production of an environmental friendly fuel that reduces the emission of greenhouse gases. Thus, bio fuel is one of the most obvious alternative sustainable fuels that can be produced from used vegetable oil and animal fats as well. Indeed, it has several advantages. For example, a biodegradable and a renewable energy reduces global warming phenomenon. Thus, this work is an attempt to produce a biodiesel fuel from chicken fat and waste cooking oil. Also, it was found that it is possible to produce biodiesel from chicken fat and waste cooking oils using transesterification reaction method. Furthermore, the process optimization was also adopted; for example, methanol to oil ratio. It has been found that the yield percentages of the produced biodiesel is increased by increasing the amount of methanol. In addition, the maximum conversion to ester could be achieved at methanol: oil ratio about 7:1. at 60 °C.